Dehydration of Byrsonima cydoniifolia A. Juss. (Canjiqueira): influence of process variables on piceatannol retention - V. S. Oliveira; J. R. Donadon; R. C. A. Guimarães; W. H. Kato Junior; T. O. Anastácio; L. M. Silva; P. O. Figueiredo; C. A. L. Cardoso; D. Bogo; V. A. Nascimento; K. C. Freitas; P. A. Hiane (Brazilian Journal of Biology)
Abstract This study evaluated the retention of piceatannol and the cytotoxicity of Byrsonima cydoniifolia A. Juss. pulp, both fresh and dehydrated, under different temperature and storage conditions. Fruits were collected in the Pantanal region (Corumbá, MS, Brazil) and dehydrated using a conventional oven at varying temperatures. Cytotoxicity was assessed using Artemia salina, murine fibroblasts, and human umbilical cord cell lines. The fresh extract showed a CL50 of 863.23 mg·L−1, classified as “low toxicity,” whereas samples dehydrated at 80 °C and 40 °C showed CL50 values of 235.28 mg·L−1 and 153.31 mg·L−1, respectively, classified as “toxic.” Despite dehydration, the fruit retained bioactive compounds, including piceatannol. After storage, the dehydrated sample maintained 71.33% of its antioxidant potential, with piceatannol, tannins, and flavonoids contents of 0.73 mg/g, 36.53 mg/g, and 25.53 mg/g, respectively. The findings support dehydration as an effective preservation method and highlight the potential functional use and valorization of native plant species.